PERPUTARAN KAS DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS DENGAN LIKUIDITAS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN SUB SEKTOR PERKEBUNAN - Eka Pratiwi Septania Parapat; Debora Silvia Hutagalung (Politeknik Bisnis Indonesia, 2023)
The purpose of his research are: 1. The description of cash turnover, inventory turnover, liquidity and profitability. 2. The effect of cash turnover and inventory turnover on profitability either simultaneously or partially. 3. The effect of cash turnover and inventory turnover on profitability with liquidity as a moderating variable This research was conducted using qualitative descriptive analysis methods and quantitative descriptive analysis. The results of this research can be summarized as follows: 1. Average Cash Turnover and Liquidity have decreased. Average Inventory Turnover and Profitability have increased. 2. The results of hypothesis testing I (multiple linear regression note that cash turnover has a positive effect, while inventory turnover has a negative effect on profitability. The results of the simultaneous test can be concluded that cash turnover and inventory turnover have a positive and significant effect on profitability. Partial test results can be concluded that turnover cash has a significant positive effect on profitability and inventory turnover has a non-significant negative effect on profitability). Hypothesis II test (Regression with Moderation variable it can be concluded that liquidity is not a moderating variable). Keywords: Cash Turnover, Inventory Turnover, Liquidity, Profitability